Library of Distributed Computing using Object Oriented Language - Phua , Ging Sheng; Tay , Choo Chuan; Ibrahim, Zulkifilie (2012)
Currently, there are Java based solutions for real time distributed computing system especially in industrial automation domain. Imagine how beneficial to extend yet adapt Java platform into automation and user can monitor yet control anything at anywhere by only using a Java based hand-held devices. This research has been done on creating a new library of distributed computing using object oriented language.